2010
DOI: 10.1021/nl902000e
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Conductance Switching in Networks of Redox-Active Molecular Junctions

Abstract: Redox-active dithiolated tetrathiafulvalene derivatives (TTFdT) were inserted in two-dimensional nanoparticle arrays to build interlinked networks of molecular junctions. Upon oxidation of the TTFdT to the dication state, we observed a conductance increase of the networks by up to 1 order of magnitude. Successive oxidation and reduction cycles demonstrated a clear switching behavior of the molecular junction conductance. These results show the potential of interlinked nanoparticle arrays as chemical sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 47 publications
0
75
0
Order By: Relevance
“…Various control experiments were performed to confirm that the switching behavior can be attributed to the oxidation of the TTF compound in the network of molecular junctions. [65] With these two examples, we demonstrate that the functionality provided by specifically-engineered molecules can be preserved in nanostructured devices where the molecules have been electrically contacted.…”
Section: Network Of Molecular Junctionsmentioning
confidence: 90%
See 3 more Smart Citations
“…Various control experiments were performed to confirm that the switching behavior can be attributed to the oxidation of the TTF compound in the network of molecular junctions. [65] With these two examples, we demonstrate that the functionality provided by specifically-engineered molecules can be preserved in nanostructured devices where the molecules have been electrically contacted.…”
Section: Network Of Molecular Junctionsmentioning
confidence: 90%
“…[59] Recently, we have shown that 2D NPs arrays form an interesting platform for molecular electronics, while based on a simple self-assembly and microcontact printing approach offering upscaling possibilities. [60][61][62][63][64][65] Fig. 4a depicts a device based on a NPs array.…”
Section: Network Of Molecular Junctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, it is demonstrated that inserting functional molecules in nanoparticles arrays can result in an overall functionality at the array Handbook of Nanoparticles DOI 10.1007/978-3-319-13188-7_27-1 # Springer International Publishing Switzerland 2015 scale. As an example, the implementation of cyclic conductance switching, thanks to redox-active molecules, is briefly discussed [38]. Starting from octanethiol (C8) covered gold nanoparticles arrays, dithiolated tetrathiafulvalene derivatives (TTFdTs) (Fig.…”
Section: From Switching Molecules To Functional Arraysmentioning
confidence: 99%